Efficacy of levofloxacin against biofilms of Pseudomonas aeruginosa isolated from patients with respiratory tract infections in vitro. Issue 5 (5th September 2018) - She, Pengfei; Luo, Zhen; Chen, Lihua; Wu, Yong
Abstract: Microbial biofilms are formed in a variety of clinical situations and increase antibiotic resistance of the pathogen by almost ~1, 000 times. The effect of levofloxacin (OFLX) on the biofilms of Pseudomonas aeruginosa strain PAO1 and the clinical isolates was investigated by crystal violet staining and confocal laser scanning microscope. The transcriptional alteration in the PAO1 biofilms upon OFLX treatment was also analyzed by RNA sequencing (RNA‐ seq ). We found that while OFLX significantly inhibited P. aeruginosa biofilm formation in a dose‐dependent manner, it could not completely eradicate preformed biofilms even at higher concentrations. RNA‐ seq revealed that PAO1 genes related to metabolism, formation of secondary metabolites, and quorum sensing biosynthesis were differentially expressed in the biofilms treated with OFLX. Our data might be useful in determining the optimum OFLX concentration needed for P. aeruginosa biofilm inhibition and eradication in patients with respiratory tract infections. Abstract : OFLX showed significant inhibitory effects on Pseudomonas aeruginosa biofilm formation in a concentration‐dependent manner. RNA‐seq revealed that the differentially expressed genes mainly related to metabolic, secondary metabolites, and quorum sensing biosynthesis when treated with OFLX. Clinical isolates from patients with respiratory tract infections were studied. \